Survival Strategies of Indonesian Immigrants in Kota Kinabalu, Sabah, Malaysia - Ibrahim Dzurizah; Jalihah Md Shah; Rose Patsy Tibok (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2019)
Findings of studies on the presence of immigrant workers in Malaysia often present negative social and economic implications. Their entry into the country is frequently a contentious issue due to their presence associated often with illegal foreign workers. This paper however is an attempt to provide insights into the involvement of Indonesian immigrants in the food business sector, their business adaptability and their survival strategies in a foreign land. The Indonesian immigrants’ experiences, from their beginnings in Sabah until their current social and community achievements, are presented in this study. Anchored on a biography study orientation and the in-depth interview method, this exploratory study examines the life experiences of five food business entrepreneurs in Kota Kinabalu, Sabah using the snowball effect as a sampling method with the subsequent data analysed thematically. Findings indicate determination and dedication as the main threads in the positive survival among Indonesian food business entrepreneurs. This study identifies seven survival strategies instrumental to the success and adaptability of the Indonesian immigrant community in their host country. Based on the findings, it can be concluded that (1) not all immigrants become liabilities to their host country and community, (2) some immigrants develop local communities by building public religious schools, and (3) some immigrants contribute to the development of local economies. The findings from this study can be utilised to develop better and more positive social and economic development overtures that could sustain a harmonious and peaceful society.